Impact of individual-risk factors on caries treatment performed by general dental practitioners. (February 2019) - Signori, Cácia; Laske, Mark; Bronkhorst, Ewald M.; Huysmans, Marie-Charlotte D.N.J.M.; Cenci, Maximiliano S.; Opdam, Niek J.M.
Abstract: Objective: This prospective study investigated how individual patient risk factors impacted non-operative and operative treatment decisions in a dental practice-based research network in The Netherlands. Methods: Data from were collected from 11 dental practices, whose patients visited the practice at least once during the observation period (January 2015 to September 2017). Descriptive analysis was performed, followed by multiple logistic regression. Results: The records of 39, 690 patients were analyzed. Approximately one-half of the population (n = 21, 056) underwent a restoration procedure during the observation period, of which 5981 (28.4%) were classified with fair oral hygiene, and 5341 (25.4%) with a high risk for caries. The population without restorative intervention (n = 18, 634) consisted mainly of patients with good oral health (n = 5132 [27.5%]) and low risk for caries (n = 7792 [41.8%]). A high risk for caries was associated with a greater chance of preventive instruction (odds ratio [OR] 1.60), applications of topical fluoride (OR 1.20) or sealants (OR 1.39), and restorative interventions (OR 5.72). There was wide variation among practices regarding the treatment provided. Conclusion: Of the 11 general dental practices that participated in this study, there was a higher chance of patients with a high risk for caries to receive preventive instructions, and professionally applied topical fluoride and sealants in the majority of practices promoting a personalized treatment approach to patients with caries. Clinical significance: A more personalized treatment approach for patients with caries was associated with a higher prevalence of high caries risk patients in the majority of practices. More studies, however, are needed to investigate whether general dental practitioners consider the assessment of individual patient risk factors in planning personalized treatment strategies.